Recent progress in chromogenic and fluorogenic chemosensors for hypochlorous acid. Issue 6 (17th February 2016) - Yue, Yongkang; Huo, Fangjun; Yin, Caixia; Escobedo, Jorge O.; Strongin, Robert M.
Abstract : Due to the biological and industrial importance of hypochlorous acid, the development of optical probes for HOCl has been an active research area. Abstract : Due to the biological and industrial importance of hypochlorous acid, the development of optical probes for HOCl has been an active research area. Hypochlorous acid and hypochlorite can oxidize electron-rich analytes with accompanying changes in molecular sensor spectroscopic profiles. Probes for such processes may monitor HOCl levels in the environment or in an organism and via bio-labeling or bioimaging techniques. This review summarizes recent developments in the area of chromogenic and fluorogenic chemosensors for HOCl.